APPLICATION OF PLATELET-RICH FIBRIN MEMBRANE IN INTRAOPERATIVE SURGICAL REPAIR OF NASAL SEPTUM PERFORATION - Loburets, A.V.; Bezega, M.I.; Loburets, V.V.; Gasiuk, Iu.A. (World of Medicine and Biology, 2024)
The article examines approaches to intraoperative closure of nasal septum perforation during septoplasty, including the use of platelet-rich fibrin membranes, which occur during septoplasty. The authors analyze the primary causes of this complication, which include mechanical damage to the mucous membrane, excessive cartilage removal, and impaired blood supply to the tissues. Comprehensive treatment was provided to 36 patients hospitalized in the Otolaryngology department for planned surgical treatment of various types of nasal septum deviation associated with impaired nasal breathing and who developed iatrogenic perforation of the nasal septum during surgery. In addition to septum perforation repair, some patients were treated with platelet-rich fibrin membranes, which involves centrifuging 10 ml of the patient’s venous blood at 2000 rpm for 15 minutes. The importance of postoperative care is emphasized, which includes regular nasal cavity moisturising, avoidance of physical activity, and prevention of infections. A personalized approach to treatment and the use of modern biomaterials improve the outcomes of perforation closure and minimize the risk of recurrence.